The effects of mirabegron on obesity‐induced inflammation and insulin resistance are associated with brown adipose tissue activation but not beiging in the subcutaneous white adipose tissue. (15th August 2021) - Peres Valgas da Silva, Carmem; Calmasini, Fabiano; Alexandre, Eduardo Costa; Raposo, Helena Fonseca; Delbin, Maria Andreia; Monica, Fabiola Zakia; Zanesco, Angelina
Abstract: Mirabegron is a selective β₃‐adrenergic receptors agonist, which has been recently shown to improve metabolic health in rodents and humans. In this study, we investigated the effects of 2‐week mirabegron treatment on the metabolic parameters of mice with a diet‐induced obesity (DIO). C57BL/6JUnib mice were divided into control (CTR) and obese (OB) groups treated with vehicle, and an OB group treated with mirabegron (OB + MIRA). The obese groups were fed a high‐fat diet for 12 weeks. Mirabegron (10 mg/kg/day) was administrated orally by gavage from weeks 10–12. After 2 weeks of mirabegron treatment, the energy expenditure was assessed with indirect calorimetry. Blood glucose, insulin, glycerol, free fatty acids (FFA), thiobarbituric acid reactive substance (TBAR), and tumour necrosis factor (TNF)‐α levels were also assessed, and the HOMA index was determined. Liver tissue, brown adipose tissue (BAT), and inguinal white adipose tissue (iWAT) samples were collected for histological examination. The protein expressions of uncoupling protein 1 (UCP1) and mitochondrial transcription factor A (TFAM) were assessed using western blotting of the BAT and iWAT samples. In this study, mirabegron increased the energy expenditure and decreased adiposity in OB + MIRA. Increased UCP1 expression in BAT without changes in iWAT was also found. Mirabegron decreased circulating levels of FFA, glycerol, insulin, TNF‐α, TBARS and HOMA index. DIO significantly increased the lipid deposits in the liver and BAT, but mirabegron partially reversed this change. Our findings indicate that treatment with mirabegron decreased inflammation and improved metabolism in obese mice. This effect was associated with increased BAT‐mediated energy expenditure, but not iWAT beiging, which suggests that mirabegron might be useful for the treatment of obesity and diabetes.